2022
DOI: 10.1029/2022gl098591
|View full text |Cite
|
Sign up to set email alerts
|

Juno Plasma Wave Observations at Ganymede

Abstract: Just prior to the end of its prime mission, Juno flew by Ganymede (Hansen et al., 2022). The flyby takes advantage of Juno's advanced instrument complement to study details of the plasma, energetic particles and fields involved in the interaction between Ganymede's and Jupiter's magnetospheres. This paper focuses on plasma waves in Ganymede's magnetosphere.Galileo plasma wave and magnetic field measurements revealed the existence of Ganymede's magnetosphere during its first flyby of the moon (Gurnett et al., 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 43 publications
5
34
0
Order By: Relevance
“…In both cases, the predicted inbound magnetopause location is very close to the simulated boundary separating Jovian and open magnetic field lines from LatHyS (Figure 2e), in agreement with Allegrini et al (2022), Kurth et al (2022), andDuling et al (2022). This is also the case for Ganymede's magnetopause location along Juno's outbound leg.…”
Section: Juno Mag and Lathys Modelsupporting
confidence: 81%
“…In both cases, the predicted inbound magnetopause location is very close to the simulated boundary separating Jovian and open magnetic field lines from LatHyS (Figure 2e), in agreement with Allegrini et al (2022), Kurth et al (2022), andDuling et al (2022). This is also the case for Ganymede's magnetopause location along Juno's outbound leg.…”
Section: Juno Mag and Lathys Modelsupporting
confidence: 81%
“…The various instruments onboard Juno detected the outbound magnetopause crossing more clearly than the inbound, matching expectations of a more dynamic magnetotail without field rotations through the magnetopause. Our model predicts that Juno left Ganymede's magnetosphere at 17:00:16, 14 s earlier than JEDI (Clark et al, 2022), 23 s earlier than JADE (Allegrini et al, 2022) and about 40 s earlier than MAG (Romanelli et al, 2022) and the Waves instrument (Kurth et al, 2022) identified the outbound crossing. Uncertain model parameters could not explain this deviation, leaving an open question for possible further required physics.…”
Section: Discussionmentioning
confidence: 79%
“…Asymmetric PADs and electron energy distributions presented in Figure 4 depict higher intensities in the downward LC (inferred from JEDI observations only) than in the upward LC. The mechanism responsible for precipitation is not addressed here, but and Kurth et al (2022) provide evidence that it may be due to the pitch angle scattering via plasma waves. Note, Figure 4b shows particle fluxes increase toward zero degrees in pitch angle, which is not consistent with quasi-linear diffusion theory through cyclotron resonances with plasma waves (e.g., Li et al, 2013;Li et al, 2021).…”
Section: Energetic Electron Signatures Prior To the First Boundary Cr...mentioning
confidence: 99%
“…The color bar scales are different between the two panels, but intensity ratios between ∼90 𝐴𝐴 • and ∼0 𝐴𝐴 • reveal that 500 keV electrons are further decimated between 5% and 70% as compared to their 50 keV counterparts. The reason for this energy dependence is unclear, but one likely candidate is energy dependent pitch angle scattering that is addressed in Kurth et al (2022).…”
Section: Features Of the Jedi Datamentioning
confidence: 99%